Steroid-triggered death by autophagy. - Thummel, C.S. (BioEssays, 2001)
Programmed cell death is a critical part of normal development, removing obsolete tissues or cells and sculpting body parts to assume their appropriate form and function. Most programmed cell death occurs by apoptosis of individual cells or autophagy of groups of cells. Although these pathways have distinct morphological characteristics, they also have a number of features in common, suggesting some overlap in their regulation. A recent paper by Lee and Baehrecke provides further support for this proposal.(1) These authors present, for the first time, a genetic analysis of autophagy, using the steroid-triggered metamorphosis of Drosophila as a model system. They demonstrate a remarkable degree of overlap between the control of apoptosis and autophagy as well as a key role for the steroid-inducible gene E93 in directing the autophagic death response. This paper also shows that E93 can direct cell death independently from the known death-inducer genes, defining a novel death pathway in Drosophila.